(untitled) (Revista Iberoamericana de Bioética, 2019)
Objectives: This study seeks to establish potential determinants in the opinion of Portuguese physicians on euthanasia, and to verify if a confrontation with concrete scenarios has an effect on this opinion. Methods: a questionnaire was distributed to physicians of various specializations with greater links to the potential practice of euthanasia. We researched the degree of agreement regarding the applicability of euthanasia to concrete situations. Results: Of a total of 251 surveyed physicians, 58.2% favored the legalization of euthanasia in Portugal. In most scenarios that included the concept of voluntary euthanasia, agreement with the applicability of euthanasia was around 55%. In scenarios where the concept of non-voluntary euthanasia was explicit, more than 60% of physicians disagreed with its application. Conclusion: It seems clear that the most relevant factor influencing the physicians’ agreement with the applicability of euthanasia is respect for the patient’s autonomy, and the existence of suffering.